AKIBAT HUKUM PENOLAKAN PENGESAHAN AKTA PENDIRIAN KOPERASI YANG DIBUAT NOTARIS OLEH KEMENTERIAN KOPERASI DAN USAHA KECIL MENENGAH (PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 28 TAHUN 2013) - DWI BUNGA ANGGRAENI SIMATUPANG (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Bismar Nasution, SH, MH2. Pro. Dr. Sunarmi, SH, MHum3. Dr. T. Keizerina Devi A, SH, CN, MHumCooperative it needs a strong legal ground relating to the deeds of cooperative such as memorandum of Associattion, the deed of the amandement of Articles of Associations, and so on. A cooperative's Memorandum of Association made by a Notary has to be approved by Minister of Cooperative since where are many amandements of its law, The research used judicial empirical method which was aimed to solve the research object by analyzing secondary data toward primary data in the field in order to find the solution of the research problems from the field on the secondary data.Keywords: Deed, Notary, Cooperative